Analysis of the prudential approaches of bank risk management : some econometric analysis on the african banks - (:unkn) unknown (My University, 2016)
This thesis contributes to the literature on prudential risk management in the banking sector,causality between financial development and economic growth and finally, the study of moral hazardand the regulation of the capital of banks. The Subprime Mortgage Crisis of 2007 paradoxicallyDépôt de thèseDonnées complémentairesmade it possible to once more highlight the inadequacies in the Basel I and Basel II prudentialstandards, because of its various consequences on the global financial system. We adopted andapplied the Granger causality test and the GMM estimation method to panel data on a sample ofbanks in sub-Saharan Africa and the Middle East, in order to conduct empirical studies, in particularon the causality between financial development and the real economy on one hand, the relationbetween capital and the profitability (risk) of banks on the other. The results highlight thedependence between certain variables describing bank profitability and economic growth on onehand, and those describing the characteristics of African banks on the other, in terms of capitalretention and excessive risk taking. This coincides perfectly with the study of moral hazard andcapital regulation set by the Basel Committee.
Keywords: African Research